Learning Styles and Self-Regulation: A Case Study of Economic Education Students at Mulawarman University - Sudarman; Ratna Fitri Astuti; Riyo Riyadi; Noor Ellyawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study identifies the relationship between learning styles and students' self-regulation in carrying out teaching practices at different levels of education. The next step is to investigate the strength of the relationship between different learning styles and different self-regulated learning skills. It was found that learning styles such as concrete experience, reflective observation, abstract conceptualisation and active experimentation have a strong relationship with students' ability to learn independently. Students with the concrete experience learning style have the ability to use cognitive strategies (0.642) and self-regulation (0.431). Reflective observation has a cognitive strategy ability of 0.522 and self-regulation of 0.453; abstract conceptualisation has a cognitive strategy ability of 0.446 and self-regulation of 0.641; and active experimentation has a cognitive strategy ability of 0.622 and self-regulation of 0.539. The conclusion of this study is that in order to develop the best competencies, pre-service teachers need high motivation to learn and good self-regulation strategies.